Perancangan Siste Data Udara Menggunakan Media Tranmsisi Serat Optis - Rudianto, Daniel (SENATIK STT Adisutjipto, 2016)
The use of optical fiber transmission media at the Air Data System is affected by the development of optical fiber technology. The system is able to present the data required by the flight crews quickly and accurately. Therefore, it supports the success of a certain mission. In addition, the air data system using the transmission medium optical fiber also has advantages other than the copper cables, i.e: immune to EMI (Electro Magnetic Interference), RFI (Radio Frequency Interference), EMP (Electro Magnetic Pulses), and will not experience any disruption caused by the occurrence of a short circuit.The fiber optic air data system is designed in consideration with the characteristics of it’s components i.e: the transmitter, optical fiber cable and the data receiver. The study also completely discusses the air data system, from the sensor, Air Data Computer (ADC), and the display of aircraft altitude and speed. .Kata kunci:    Serat optis, sistem data udara, air data computer.